Gender-aware inclusive value chain: A theoretical perspective - Kini, Janvier (Frontiers in Sustainable Food Systems, 2022)
Achieving the SDG5 an analytical and practical framework enabling a win-win participation of poor resources women in gender blind societies. Poor resources women are mostly excluded from formal economic system and face gender inequality. In agricultural and food value chains, women are not equally included as men in highly attractive value chains so they end-up in informal (less lucrative) agri-food activities alongside the value chains. However, existing literature fails to design an adequate framework that efficiently addresses gender inequality and poverty conditions of women in low-income countries mostly gender-blind. This paper contributes to fill in this gap in knowledge by proposing a gender-aware inclusive value chain. For this purpose, we conducted a deep and extensive state-of-art on value chains development and strategies over the past three decades. Two main types are drawn from this literature review: 1) conventional value chains, mainly exclusive or adversely include the bottom of the pyramid populations and gender-blind; 2) gender-aware value chains mostly focused on value chains that controlled by women. Hence, the paper proposes a third type of value chains inspired by the Foucauldian perspective of human being: gender-aware inclusive value chain (GAIVC). In this perspective, we consider a value chain as similar to human body in its functioning. As human body is composed of different organs that are autonomous, but complementary each other. GAIVC is also composed of different elements (actors/stakeholders, farms, storages, infrastructures and so on) that should be complementary and no competitive. In this perspective, it gives more opportunities to poor resource women to evolve in non-discriminatory environment based on gender. It also breaks down the power relations between the chain actors are they have to cooperate and avoid the chain to collapse from within and outside threats. This way, the sustainability of value chains is guaranteed and all actors involved have fair rewards from the chain participation.